Adopsi Inovasi Budidaya Melon (Cucumis Melo L.) Dengan Teknologi Greenhouse Di Kecamatan Wates Kabupaten Blitar - Cahyani, Riza Dwi; Hidayat, Kliwon; Kustanti, Asihing (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
Climate change is a major factor that can threaten sustainable food production, and efforts have been put in place to prevent potential food shortages in the future. One of the mitigations and adaptations carried out by farmers in Wates District, Blitar Regency is adopting greenhouse technology in melon cultivation. This research was conducted to analyze the process of adoption of greenhouse innovations in melon cultivation in Wates District, Blitar Regency. This study uses a qualitative approach. Data were collected by observation, in-depth interviews, documentation and literature studies using purposive sampling techniques to determine informants and snowball sampling to determine supporting informants. The result of this research is that the greenhouse innovation in melon cultivation has been successfully adopted from the knowledge stage to the confirmation stage, because it is considered according to the needs of farmers. The word-of-mouth system is a system for disseminating initial information. It is also known that Facebook, Instagram, and YouTube are the communication channels used to disseminate greenhouse innovations. Farmers' ability to use greenhouses influences their view of innovation characteristics.